Breaking the flow: a study of contradictions in information systems development (ISD). Issue 2 (5th August 2019) - Dennehy, Denis; Conboy, Kieran
Abstract : Purpose: The purpose of this paper is to examine contradictions (specifically tertiary and quaternary contradictions) that can disrupt the flow of work in contemporary systems development methods. Design/methodology/approach: This study uses Activity theory (AT) as a theoretical lens to: examine ISD flow as an interrelated activity system; and identify contradictions. AT is pertinent in the context of this study as rather than view contradictions as a threat to prematurely abandon the use of flow tools and metrics, it shows how contradictions can act as a motor for change and continuity. This study adopts a longitudinal single case study approach including face-to-face interviews with management and software development project teams, as well as direct observations and document analysis. Findings: This study identifies tertiary and quaternary contradictions, and highlights the influence of contradictions on flow-based systems development. Social implications: This study provides a set of contradictions for researchers and practitioners. It shows that contradictions can be culturally or politically challenging to confront, and even when resolved, can have intended or unintended consequences. Originality/value: This paper fulfils an identified need to study ISD flow from the perspective of interrelated activity systems and beyond its initial implementation phase.